Pengetahuan tentang HIV/AIDS dan Voluntary Counseling and Testing (VCT), Kesiapan Mental, dan Perilaku Pemeriksaan di Klinik VCT pada Para Mitra Pengguna Obat dengan Jarum Suntik di Surakarta - Wicaksana, Junitha Fitri Putri; Kusumawati, Yuli; Ambarwati (Jurnal Kedokteran Indonesia, 2009)
Background : HIV/AIDS can be transmitted through unsterile syringe. Therefore intravenous drug user(IDU) partners are at high risk to get HIV/AIDS infection. This study aimed to determine the associationbetween knowledge on HIV/AIDS, VCT, and mental readiness, and the willingness to undertake VCTamong IDU partners at VCT clinic in Surakarta.Methods : This was a cross-sectional study. The source population was 99 IDU partners visiting VCTClinic in Surakarta. A sample of 18 IDU steady and 60 IDU temporary partners were selected at randomfor this study. The data was analyzed by use of chi square test on SPSS 16.Results : Data analysis showed a statistically significant association between knowledge on VCT (p=0.005) but no statistically significant association between mental readiness (p= 0.956), respectively,and the willingness to undertake VCT among IDU partners in Surakarta.Conclusion : There is assocition between knowledge on VCT and willingness to undertake VCT amongIDU partners. There is no association between mental readiness and willingness to undertake VCT.Keywords : HIV/AIDS, Intravenous drug user (IDU) partners, VCT